Development of Online Education: Technological Innovations and Challenges for Higher Education Institutions (Acta Education, 2024)
The article explores the dynamics of the development of online education and its impact on higher education institutions. Particular attention is paid to technological innovations that are shaping modern teaching practices and transforming the way learning and learning are assessed. The article also analyzes the challenges that universities face in integrating online education into their operations, such as ensuring the quality of the educational process, managing data and privacy, and making online education accessible to different groups of students. As a result of the study, recommendations are offered for the effective implementation of online education in higher education, taking into account modern technological trends and the needs of students and teachers.